RETRACTED: ESMO Guidance for reporting oncology real-world evidence (GROW) - A. Sh. Motrinchuk; A. A. Kurylev (Реальная клиническая практика: данные и доказательства)
RETRACTED ARTICLEThe European Society for Medical Oncology (ESMO) has produced the very first expert-based guidance for reporting real-world evidence (RWE) studies specifically for oncology. The publication addresses nuances of modern RWE research in oncology and provides a comprehensive list of detailed key recommendations — that have also been transcribed into an interactive informative scoring checklist tool — for full article development in different RWE research scenarios.